HUBUNGAN ANTARA KUALITAS PRODUK DAN KUALITAS LAYANAN DENGAN KEPUASAN PELANGGAN PADA PERUSAHAAN DAGANG ADZA CATERING KOTA BOGOR - Nia Sonani; Hari Muharam; Ferdisar Adrian (JIMFE (Jurnal Ilmiah Manajemen Fakultas Ekonomi), 2017)
ABSTRACTThis research is included as a correlational research, and consisted of two independent variables and one dependent variable, i.e. product quality and service quality with customer satisfaction. The research was conducted on customer of Adza Catering, with samples of 100 customers, derived by random sampling. The method used was survey and data analysis technique using statistical test of correlation and linear regression. The hypothesis testing was conducted at the significant level of ? = 0.05. The results yield three conclusions, namely: first, there is a highly significant positive relationship between product quality and customer satisfaction with a correlation coefficient ry1 of 0.647, coefficient of determination of 0.4186 and the regression equation is ?= 56.220 + 0.419X1. Second, there is a highly significant positive relationship between service quality and customer satisfaction with correlation coefficient ry2 of 0.763, coefficient of determination of 0.5821 and the regression equation is ? = 40.773 + 0.376X2. Third, there is a highly significant positive relationship between product quality and service quality together simultaneously with customer satisfaction with a correlation coefficient Ry.1.2 of 0.740, coefficient of determination of 0.5476 and the regression equation is ?= 22.612 + 0.428X1 + 0,236X2. Based on these results, it can be concluded that product quality and service quality provide highly significant contribution to customer satisfaction.Keywords: Product Quality, Service Quality and Customer Satisfaction